Utilization of Social Media as An Effort to Improve the Competitiveness of Islamic Educational Institutions - Farwati, Wiwik Wida (Education and Sociedad Journal, 2024)
This study aims to determine the transformation of educational marketing strategies as an effort to increase the competitiveness of Islamic educational institutions. This study focuses on how the existence of Islamic educational institutions in multicultural areas. The method used in this study is qualitative research with a phenomenological research type. The results of the research data were then analyzed using thematic analysis according to Braun & Clarke. The results of the study show that social media has greatly influenced consumer behavior and has become a pioneer in educational institution marketing strategies in the current digital era. On the other hand, Institutions that successfully integrate social media into digital marketing strategies like TikTok and Instagram will tend to achieve greater success in achieving marketing goals. This study makes a significant contribution by introducing a new approach to educational marketing that is relevant to current technological developments.